CHARACTERIZATION ANALYSIS FOR SEDIMENT MANAGEMENT IN GROGOL RIVER - Nurhawa, Arni; Budianto, Bambang Setio; Windari, Aulia Choiri (PT. Hafasy Dwi Nawasena, 2025)
Abstract This study analyzed the grain size distribution and physical characteristics of the Grogol River bed sediment, Grogol Petamburan District, West Jakarta. This river plays an important role in the urban drainage system, but sediment accumulation causes siltation and a decrease in its capacity, thus increasing the risk of flooding during the rainy season. This study aims to provide technical data for sedimentation control. The method used is quantitative with laboratory tests, including grain size analysis (sieve analysis), specific gravity test, and water absorption. Sediment samples were taken from the river bed at certain points, then dried, sieved, and weighed. The analysis refers to SNI 03-1968-1990 and ASTM C-33. The results showed that 45% of the sediment material passed the No. 200 sieve (0.075 mm), classified as Clayey Sand (SC) according to the Unified Soil Classification System (USCS). The grain size distribution is classified as poorly graded, indicating an uneven and homogeneous size distribution, thus accelerating sedimentation. The fine fraction exceeds the ASTM limit which allows a maximum of 3% to pass the No. 200 sieve for fine aggregate. The bulk specific gravity value of 2.353 gr/cc, bulk SSD specific gravity of 2.415 gr/cc, apparent specific gravity of 2.510 gr/cc, and absorption of 2.7% indicate moderate porosity. These characteristics affect sediment stability and movement, especially when the flow rate changes. Overall, the Grogol River sediment has the potential to accelerate sedimentation, worsen siltation, and reduce the river's hydraulic capacity. These findings form the basis for planning mitigation strategies such as normalization, routine dredging, settling ponds, and adaptive drainage management according to local sediment characteristic